In-Depth Analysis of Urrent Infection Prevention and Control Practices in Class C Military Hospitals of Pakistan - Ehsan, Ayesha; Ehsan, Fatima; Hanif, Hamad (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the current Infection Prevention and Control practices in Class C Military Hospitals of Pakistan.Study Design: Mix-method study.Place and Duration of study:  Pakistan Navy Shifa Hospital, Karachi, Pakistan, from Jan to Dec 2023.Methodology: Three hospitals (corresponding to primary level) were selected from a total of ten, through random sampling. Data was collected using infection prevention and control assessment framework (IPCAF) tool which comprises of eight sections with a 100 score in each. Based on these scores, in-depth semi structured interviews from the focal person representing highest and lowest scoring hospitals were then conducted. Participants' responses were recorded during the interview. We typed and examined the coded script with eight themes.Results: Out of a total of 800, the median score of the three hospitals was 632.5 with a mean of 543.3. One Class C hospital fell into adequate category with a score of 227.5 and the other two in advanced level with a score of 632.5 and 770. However, in depth interviews of the highest and lowest scoring hospitals showed significant difference in pre and post interview scores. This highlighted the gap in comprehending the Infection Prevention and Control Assessment Framework (IPCAF) by the designated infection prevention and control (IPC) focal person.Conclusion: The sampled Class C Military hospitals demonstrated a varied but satisfactory infection prevention and control (IPC) level. Challenging areas observed were education and training, surveillance, monitoring/audit and staffing.